OPTIMIZATION FEEDING RATE OF SPINY LOBSTER (Panulirus penicillatus) CULTURED IN FLOATING CAGES - Mahmudin, Muhammad Nasir; Utomo, Deny Sapto Chondro; Elisdiana, Yeni; Brite, Margie; Adiputra, Yudha Trinoegraha (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2021)
Spiny lobster (Panulirus penicillatus) is one of luxury seafood product that cultured in floating cage. There is no information about feeding rate of this species in particular feed with fresh mangrove snail meat. This study aimed to optimized level of feeding rate in spiny lobster during limited periods of cultured. Feeding rate of 10, 20 and 30% were used as treatments. Three floating cages with 120 individuals of pre-adult of spiny lobster was used. Sixty days of cultured periods with absolute growth, specific growth rate and survival rate were analysed to determined optimized growth rate. Results showed that 10% of feeding rate was supported highest absolute growth and specific growth rate compared to 20% and 30 % feeding rate. Moreover, all level of feeding rate can support 100 % of survival rate. This study recommends feeding rate 10% is sufficient feed percentage per day that able to support culture performance of spiny lobster grow-out in floating cage.